Development of an FgMito assay: a highly sensitive mitochondrial based qPCR assay for quantification of Fusarium graminearum sensu stricto - Kulik, Tomasz (2015)
An ascomycete fungus, Fusarium graminearum sensu stricto (s.s.), is the major cause of Fusarium head blight (FHB), a devastating disease of cereals worldwide. The fungus contaminates crops with mycotoxins, which pose a serious threat to food and feed safety. In this study, we developed a highly sensitive mitochondrial based qPCR assay (FgMito qPCR) for quantification of F. graminearum s.s. To ensure high sensitivity of the assay, primers and a Minor-groove binding (MGB) probe were designed based on multi-copy mitochondrial DNA. The FgMito assay was successfully validated against a range of geographically diverse F. graminearum s.s. strains to ensure uniformity of the assay at an intraspecific level, as well as with other fungal species to ensure specificity. The assay was further evaluated in terms of efficiency and sensitivity against a test panel of different F. graminearum s.s. strains with various levels of pure fungal DNA and in the presence of wheat background DNA. The results showed a high efficiency of the assay developed, ranging from 93% to 101% with r2-values of > 0.99. We further showed that three low concentrations of fungal template 2 pg, 0.6 pg and 0.2 pg could be reliably quantified in the presence of wheat background DNA. The FgMito assay was used to quantify F. graminearum s.s. DNA on 65 field samples from a range of hosts with defined levels of trichothecenes. We revealed a significant positive correlation between fungal DNA quantity and the sum of trichothecenes. Lastly, we showed a higher sensitivity of the FgMito assay than the nuclear based qPCR assay for F. graminearum s.s. by comparing Ct-values from both assays.